Combinatory actions of cytokines induce M2-like macrophages in anaplastic thyroid cancer - Kimura, Takahito (2024)
Anaplastic thyroid cancer (ATC) is a lethal endocrine malignancy. It has been shown that tumor-associated macrophages (TAMs) contribute to the aggressiveness of ATC. However, stimulatory factors that could facilitate the induction and infiltration of TAMs in the ATC tumor microenvironment (TME) are not fully elucidated. In this study, we used a human leukemia monocytic cell line (THP-1) to study the differentiation of THP-1 into M2-like macrophages (M2) by conditioned media (CM) derived from each of the three human ATC cells: 8505C, THJ-11T (11T), and THJ-16T (16T). The capacity of CM to induce M2 was in the order of 16T>8505C>11T cells as determined by the expression of M2 markers (CD163, CD204, and CCL13). Cytokine arrays and ELISA assays revealed five commonly enriched cytokines (IL-6, IL-8, MCP-1, TIMP-1, and TGF-β1) in the CM derived from each of the three ATC cells. These cytokines, individually, had weak activity, but together, they mimicked full CM activity in the induction of M2. Further, they collaboratively activated STAT3, ERK, and PI3K-AKT signaling to facilitate the induction of M2 as found in CM. Importantly, we found that the CM-induced M2 could secrete soluble growth factors to promote ATC cell proliferation as evidenced by the increased Ki-67, cMYC, and cyclin D1 protein levels. Our studies identified the major stimulatory cytokines which acted collaboratively to induce M2 in the TME. Importantly, the present studies indicate that when using inhibitors to target TAMs, combination therapies would be required for effective treatment of ATC.